2017
DOI: 10.1016/j.neuron.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Axon Death Pathways Converge on Axundead to Promote Functional and Structural Axon Disassembly

Abstract: Axon degeneration is a hallmark of neurodegenerative disease and neural injury. Axotomy activates an intrinsic pro-degenerative axon death signaling cascade involving loss of the NAD biosynthetic enzyme Nmnat/Nmnat2 in axons, activation of dSarm/Sarm1, and subsequent Sarm-dependent depletion of NAD. Here we identify Axundead (Axed) as a mediator of axon death. axed mutants suppress axon death in several types of axons for the lifespan of the fly and block the pro-degenerative effects of activated dSarm in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
154
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(159 citation statements)
references
References 64 publications
5
154
0
Order By: Relevance
“…The expression of the Wld s protein is the most studied model of delayed axonal degeneration (Mack et al, 2001;Adalbert et al, 2005;Hoopfer et al, 2006). Loss-of-function studies have also identified mutants that exhibit Wld s -like protection of severed axons, such as dSarm/ Sarm1 (Osterloh et al, 2012;Essuman et al, 2017) and Axundead (Neukomm et al, 2017), supporting the idea that Wallerian degeneration is indeed an active and regulated process.…”
Section: Introductionmentioning
confidence: 93%
“…The expression of the Wld s protein is the most studied model of delayed axonal degeneration (Mack et al, 2001;Adalbert et al, 2005;Hoopfer et al, 2006). Loss-of-function studies have also identified mutants that exhibit Wld s -like protection of severed axons, such as dSarm/ Sarm1 (Osterloh et al, 2012;Essuman et al, 2017) and Axundead (Neukomm et al, 2017), supporting the idea that Wallerian degeneration is indeed an active and regulated process.…”
Section: Introductionmentioning
confidence: 93%
“…NAD is an essential co-enzyme for several biological process, such as cell death, energy metabolism and calcium mobilization. NMNAT2 is highly expressed in the brain, and along with axon protection following injury (44)(45)(46)(47)(48)(49) is implicated in neurodegenerative disease (50)(51)(52)(53). While functional genetics indicate PHR proteins can inhibit NMNAT2, the biochemical mechanism by which this occurs remains untested.…”
mentioning
confidence: 99%
“…We next asked whether TIR-1 might direct multiple responses to injury by activating different downstream signaling events in each axon fragment. TIR-1 and SARM1/dSarm execute several cellular functions, including cleavage of NAD + , activation of MAPK signaling and the Axundead protein, as well as regulation of calcium signaling, gene transcription and autophagy (14,15,24,25,28). This informed a candidate approach to dissect the genetic pathways in which TIR-1 regulates both axon regeneration and degeneration.…”
Section: Tir-1 Regulates Axon Regeneration With the Nsy-1 -Pmk-1 Mitomentioning
confidence: 99%
“…On the distal side of the injury, the most notable endogenous regulator of axon degeneration is Sterile Alpha and Toll/interleukin-1 resistance (TIR) Motif Containing 1 (SARM1/dSarm), which is essential for injury-induced axon degeneration of Drosophila and mouse axons (12,13). SARM1/dSarm promotes axon degeneration cell-autonomously, by depleting NAD + and ATP, interacting with the BTB/BACK domain protein Axundead, and by interacting with mitogenactivated protein kinase (MAPK) signaling cascades, which in turn regulate calpain activation, SCG10/Stathmin 2 proteolysis, mitochondrial dysfunction, cytoskeletal disruption, and axon fragmentation (14)(15)(16)(17)(18)(19)(20)(21). Whether the C. elegans SARM1/dSarm homolog, TIR-1, also regulates injury-induced axon degeneration is not known; however, in the absence of injury, SARM1, dSarm, and TIR-1 promote disease-and age-associated neurodegeneration (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%